The regulation of gastric acid secretion – clinical perspectives. (27th December 2013) - Waldum, H. L.; Hauso, Ø.; Fossmark, R.
Abstract The purpose of this review, based upon 40 years of research, is to clear old controversies. The gastric juice is a strong acid with active enzymes (pepsin and lipase); ideal for killing swallowed microorganisms. Totally isolated rat stomach and histamine determination. Human gastric carcinomas were examined for ECL cell differentiation because tumours found in rodents after dosing with inhibitors of acid secretion were reclassified to be of ECL cell origin. The gastrin receptor is localized to the ECL cell only, where gastrin stimulates the function and growth. Drug‐induced hypo‐acidity induces hypergastrinaemia and ECL cell hyperplasia responsible for rebound acid hypersecretion. Every condition with long‐term hypergastrinaemia disposes to ECL cell neoplasia. In man, both atrophic gastritis and gastrinoma lead to ECL cell carcinoids. Proton pump inhibitors induce hypergastrinaemia with ECL cell hyperplasia and ECL cell carcinoids that disappear when stopping treatment. The gastrin antagonist netazepide induces regression of ECL cell carcinoids due to atrophic gastritis. Human gastric carcinomas of diffuse type, particularly the signet‐ring subtype, show ECL cell differentiation, suggesting involvement of gastrin in the carcinogenesis. Helicobacter pylori (Hp) causes gastritis and peptic ulcer, and when infecting the antrum only gives a slight hypergastrinaemia with acid hypersecretion predisposing to duodenal ulcer, but protecting from gastric cancer. When Hp infection spreads to oxyntic mucosa, it induces atrophy, reduced acid secretion and marked hypergastrinaemia and cancer.It is remarkable that the interaction between Hp and gastrin may explain the pathogenesis of most diseases in the upper gastrointestinal tract.